Ciclos limite em sistemas lineares por partes apresentando dois focos virtuais - Cruz, Leonardo Pereira Costa da [UNESP] (2014)
In this work we study planar piecewise linear systems in two zones. A straight line through the origin separates the plane into two zones. In each zone we consider a linear system, not necessarily with singularity at the origin. This class system has twelve parameters. The main reference for this work is the paper [6] E. Freire, E. Ponce and F. Torres. Using an appropriate change of coordinates, the particular focus-focus case is reduced to just ve parameters. The main goal is to characterize the number of limit cycles in terms of the ve parameters of the system. The main technique used for the study is the Poincar e rst return map. For the case where the system has no sliding on the line of separatation the conclusion is that the system has at most one limit cycle. For the case with sliding motion, and considering that the foci are virtual, the conclusion is that the system has at most two limit cycles